Pre-diagnosis leukocyte telomere length and risk of ovarian cancer - Yang, Meng (Cancer Epidemiol Biomarkers Prev, 2017)
BACKGROUND: The associations between telomere length and cancer risk are equivocal, and none have examined the association between pre-diagnosis leukocyte telomere length and the risk of developing ovarian cancer. METHODS: We prospectively measured leukocyte telomere length (LTL) collected from 442 ovarian cancer cases and 727 controls in the Nurses’ Health Studies and the Northern Sweden Health and Disease Study. Cases were matched to one or two controls on age, menopausal status, and date of blood collection. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using conditional logistic regression. RESULTS: LTL was measured a median of 9.5 years before ovarian cancer diagnosis among cases. We observed a decreased risk of ovarian cancer with longer LTL. In multivariable models, women in the top quartile of LTL had an OR for ovarian cancer of 0.67 (95% CI=0.46–0.97) compared to those in the bottom quartile. Inverse associations were stronger for non-serous cases (OR(quartile 4 vs. quartile 1 of LTL)=0.55, 95%CI=0.33–0.94) and rapidly fatal cases (i.e. cases who died within 3 years of diagnosis) (OR(quartile 4 vs. quartile 1 of LTL)=0.55, 95%CI=0.32–0.95). CONCLUSION: Our prospective findings suggest that longer circulating LTL may be associated with a lower ovarian cancer risk, especially for non-serous and rapidly fatal cases. The evaluation of LTL in relation to ovarian cancer risk by tumor subtypes is warranted in larger prospective studies. IMPACT: Pre-diagnosis LTL may reflect an early event in the ovarian cancer development and could serve as a biomarker to predict future risk.